Improved ecological insights commission new conservation targets for a crepuscular bird species. (7th October 2020) - Evens, R.; Jacot, A.; Artois, T.; Ulenaers, E.; Neyens, T.; Rappaz, L.; Theux, C.; Pradervand, Jean‐Nicolas
Abstract: Knowledge on species' ecological requirements is the key to an effective evidence‐based conservation. An adaptive approach can refine management recommendations following the outcomes of previous actions or as improved scientific knowledge about a species' ecology becomes available. Following severe population declines the majority of the Swiss European Nightjar ( Caprimulgus europaeus) population is now restricted to a small core area in the canton of Valais, despite the local application of evidence‐based restoration measures to the breeding habitats. The habitat use of this crepuscular bird species is presumed to be restricted to semi‐open oak‐pine scrublands and rocky steppe. By deploying miniature GPS loggers we assessed the spatial and habitat selection of 42 individuals (25 individuals in 2018 and 30 individuals in 2019; comprising 13 redeployments between years) in five study sites in the canton Valais. We highlight the importance of using fine‐scaled movement data to obtain insight into complex multi‐scale habitat requirements of a species. Nightjars used multiple habitats, indicating the importance of complementary resources to breed (e.g. open forest and shrub) and to forage (e.g. semi‐extensive grasslands and vineyards). The connectivity between these resources was influenced by habitat configuration and composition. Given these new insights for future conservation strategies, our results also suggest that national‐level land use changes, mainly due to agricultural intensification processes, have contributed to the long‐term population declines in Switzerland. We therefore consider our result in the context of knowledge gaps for species that exploit complementary habitats and the potential shortcomings for conservation planning on discrete species showing complex ecological requirements. Abstract : Following severe population declines the majority of the Swiss European Nightjar ( Caprimulgus europaeus ) population is now restricted to a small core area in the canton of Valais, despite the local application of evidence‐based restoration measures to the breeding habitats. By deploying miniature GPS‐loggers, we assessed the spatial and habitat selection of 42 individuals (25 individuals in 2018 and 30 individuals in 2019; comprising 13 redeployments between years) in five study sites in the canton Valais. Nightjars used multiple habitats, indicating the importance of complementary resources to breed (e.g. open forest and shrub) and to forage (e.g. semi‐extensive grasslands and vineyards), highlighting potential shortcomings of current conservation practices of this discrete species with complex ecological requirements.